Human Ontogeny of Drug Transporters: Review and Recommendations of the Pediatric Transporter Working Group. Issue 3 (September 2015) - Brouwer, KLR; Aleksunes, LM; Brandys, B; Giacoia, GP; Knipp, G; Lukacova, V; Meibohm, B; Nigam, SK; Rieder, M; de Wildt, SN; on behalf of the Pediatric Transporter Working Group; Abdel‐Rahman, Susan; et al.
<x xml:space="preserve">Abstract</x> The critical importance of membrane‐bound transporters in pharmacotherapy is widely recognized, but little is known about drug transporter activity in children. In this white paper, the Pediatric Transporter Working Group presents a systematic review of the ontogeny of clinically relevant membrane transporters (e.g., SLC, ABC superfamilies) in intestine, liver, and kidney. Different developmental patterns for individual transporters emerge, but much remains unknown. Recommendations to increase our understanding of membrane transporters in pediatric pharmacotherapy are presented.